Subunit structure of cell surface proteins: disulfide bonding in antigen receptors, Ly-2/3 antigens, and transferrin receptors of murine T and B lymphocytes. - Goding, J W (1981)
The surface proteins of lymphocytes from spleen and thymus and several cultured lymphoid tumor lines were radioiodinated in situ, solubilized with Triton X-100, and examined for the presence of disulfide-bonded subunits by two-dimensional (intact, reduced) NaDodSO4/polyacrylamide gel electrophoresis. [Hynes, R. O. & Destree, A. (1977) Proc. Natl. Acad. Sci. USA 74, 2855-2859]. Few lymphocyte surface proteins were found to consist of disulfide-bonded subunits, and the most prominent of these could be identified. In normal B lymphocytes and B-lymphoma cells, IgD or IgM (or both) were the major disulfide-bonded proteins, and these were easily detectable, even without immunoprecipitation. In contrast, analysis of thymocytes and T-lymphoma cells did not reveal any protein resembling immunoglobulin in its chain structure. The major labeled thymocyte membrane protein consisting of disulfide-bonded subunits was identified as the Ly-2/3 antigen. It appeared to contain disulfide-bonded homodimers of Mr 35,000 (alpha 2) noncovalently associated with a second pair of homodimers of Mr 30,000 (beta 2). Peptide mapping showed these polypeptides to be homologous. A third disulfide-bonded homodimer, which was heterogeneous in apparent Mr, appeared to be part of the Ly-2/3 complex. All cultured T- and B-lymphoma lines examined were found to possess a major surface protein that appeared to be a disulfide-bonded homodimer of a polypeptide of Mr 95,000. This protein was identified as the receptor for transferrin. It is suggested that the presence of two or more subunits in cell surface receptors renders their ligand functionally bivalent, making ligand-induced receptor aggregation possible.